2020
DOI: 10.3389/fmicb.2019.02855
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Potential Novel Probiotics With Dipeptidyl Peptidase IV-Inhibiting Activity for Type 2 Diabetes Attenuation in vitro and in vivo

Abstract: Diabetes has become the second most severe disease to human health. Probiotics are important for maintaining gastrointestinal homeostasis and energy balance and have been demonstrated to play a positive role in the prevention and treatment of metabolic syndromes, such as obesity, inflammation, dyslipidemia, and hyperglycemia. The objective of this study was to screen potential antidiabetic strains in vitro and evaluate its effects in vivo. For the in vitro section, dipeptidyl peptidase IV (DPP-IV) inhibitory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 88 publications
2
31
0
4
Order By: Relevance
“…Moreover, to date, a large amount of evidence has shown that some lactic acid bacteria have an effective anti-obesity effect in animal research and clinical research (Dahiya et al, 2017). Previous researches in our laboratory have demonstrated that L. plantarum KLDS1.0344 and L. plantarum KLDS1.0386 have strong acid and bile salt resistance, high cell adhesion activities and lipid metabolism regulation properties (Tang et al, 2016;Jin et al, 2017;Lu et al, 2018;Yan et al, 2019;Yue et al, 2019). Therefore, further researches were carried out and it was found that mixed lactobacilli (L. plantarum KLDS1.0344 and L. plantarum KLDS1.0386) could prevent the formation of obesity in high fat diet-fed mice , which confirmed the probiotic properties of the mixed lactobacilli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, to date, a large amount of evidence has shown that some lactic acid bacteria have an effective anti-obesity effect in animal research and clinical research (Dahiya et al, 2017). Previous researches in our laboratory have demonstrated that L. plantarum KLDS1.0344 and L. plantarum KLDS1.0386 have strong acid and bile salt resistance, high cell adhesion activities and lipid metabolism regulation properties (Tang et al, 2016;Jin et al, 2017;Lu et al, 2018;Yan et al, 2019;Yue et al, 2019). Therefore, further researches were carried out and it was found that mixed lactobacilli (L. plantarum KLDS1.0344 and L. plantarum KLDS1.0386) could prevent the formation of obesity in high fat diet-fed mice , which confirmed the probiotic properties of the mixed lactobacilli.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus plantarum KLDS1.0344 and L. plantarum KLDS1.0386 were isolated from traditional fermented dairy products in Inner Mongolia, China, and preserved in our laboratory. In addition, our previous studies have demonstrated that L. plantarum KLDS1.0344 and L. plantarum KLDS1.0386 have strong acid and bile salt resistance, high cell adhesion activities and lipid metabolism regulation properties (Tang et al, 2016;Jin et al, 2017;Lu et al, 2018;Yan et al, 2019;Yue et al, 2019). Hence, we investigated whether a mixture of L. plantarum KLDS1.0344 and L. plantarum KLDS1.0386 could prevent obesity.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, probiotics' therapeutic potential against T2DM is based on the improvement of the gut barrier function, the increase in insulin sensitivity and critins levels, the reduction in serum lipopolysaccharides levels, as well as the oxidative and endoplasmic reticulum stress amelioration. L. acidophilus KLDS1.0901 is a novel promising antidiabetic probiotic strain, as demonstrated by in vitro dipeptidyl peptidase IV inhibitory activity along with increased blood glucose level balance and retarded insulin resistance and oxidative stress (Yan et al, 2020). Zhang et al (2020) screened the in vitro efficacy of three strains (L. paracasei 1F-20, L. fermentum F40-4, and B. animalis subsp.…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…As probiotics, some LABs have improved health and prevented infection activities facilitated by enteropathogenic bacteria ( Bian et al, 2015 , 2016 ). However, because of strain-specific effects, only selected LAB candidates obtained from initial screening protocols are further studied ( Yan et al, 2020 ). The current study evaluated the antimicrobial effects of the CFS of L. bulgaricus KLDS 1.0207 against two foodborne pathogens after subjection to enzymatic actions and pH changes.…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated in many previous studies involving Lactobacillus, Bifidobacterium, and Streptococcus strains ( Thantsha et al, 2012 ; Ashraf and Smith, 2016 ; Evivie et al, 2017 ; Tang and Zhao, 2019 ). A recent study assessing the biological and antidiabetic properties of Lactobacillus strains (including L. bulgaricus KLDS 1.0207) demonstrated that their acid and bile tolerant properties have the potentials for adhesion to or colonization of host intestine, which could endow them with anti-diabetic properties ( Yan et al, 2020 ). Furthermore, in evaluating the tolerance levels of several promising commercial strains, Ashraf and Smith (2016) recently showed that some Lactobacillus bulgaricus strains could survive effectively under acid and bile conditions for up to 12 h, which again demonstrates the efficacy of specific strains to function as potential probiotics.…”
Section: Discussionmentioning
confidence: 99%